AN ANALYSIS OF SUSTAINABLE COMPETITIVE ADVANTAGE AND ENVIRONMENTALLY FRIENDLY MARKETING MODELS IN NATURAL DYES AND BATIK AND ECOPRINTING MSMEs - Tri Wahyu Lestari; Adi Sucipto; Wakhdan Wakhdan (SEGMEN: Jurnal Manajemen dan Bisnis, 2026)
This research aims to examine the influence of green knowledge management, ecological innovation, and ecological commitment on sustainable competitive advantage and sustainable marketing performance among batik and natural-dyed ecoprint MSMEs in Purworejo Regency. The study addresses the problem of low integration of sustainable business practices and limited use of local natural resources, which challenge MSMEs in responding to global market demands and environmental regulations. A quantitative explanatory survey was conducted with 100 SMEs selected by purposive sampling. Data were analyzed using Partial Least Squares – Structural Equation Modeling (SEM-PLS). The results show that green knowledge management, ecological innovation, and ecological commitment have significant positive effects on sustainable competitive advantage and green marketing performance. In addition, sustainable competitive advantage mediates the relationship between these factors and green marketing outcomes, providing important implications for MSME development in eco-friendly industries.